New dengue antibody assay with unique differential detection of IgG and IgM antibodies (2009)
Most of the serological methods, traditional and recent, that have been developed to assess laboratory confirmation of dengue infection, suffer from the need to use separate tests for IgM and for IgG and the need for paired serum specimens in order to establish a clinical interpretation. Moreover, most of the IgG tests ignore early convalescence as well as past exposure. The objectives of this study is to demonstrate the advantages of the ImmunoComb Dengue BiSpot, a new dengue antibody assay, that detects simultaneously both dengue-specific IgM and IgG, in determining type and status of infection in a single test. Single and paired positive and negative specimens obtained from various dengue-high prevalent regions and from dengue-free areas were used. The specimens were comprised of admission samples of suspected patients and secondary dengue infection individuals, a group of hospital patients, asymptomatic to dengue who originated from dengue high prevalence areas and dengue-negative volunteers. All samples were tested by the ImmunoComb Dengue BiSpot kit along with the gold standard assays of Hemagglutination-inhibition (HAI) and MAC ELISA. Testing 365 gold standard positive specimens from different regions, the ImmunoComb Dengue BiSpot kit revealed sensitivity for IgM of 97.5% and 99.1% for IgG. The IgG was segregated into 2 groups: 86.6% for high titer and 12.5% for low titer of IgG. The overall sensitivity was 98.9%. The overall specificity of the kit, testing 657 samples, mostly from dengue-free area was 97.9%. The higher diagnostic resolution of the Dengue BiSpot test was demonstrated when the performance of the kit on the various groups was compared to the gold standard tests and the dengue status was determined in paired specimens by the new assay. The results of the present studies demonstrate the advantages of ImmunoComb Dengue BiSpot assay as an alternate strategy for the determination of dengue infection status. The combined use of IgM and IgG to discriminate between primary and secondary infections, on one hand, and providing high resolution in distinction of convalescence stage and past infection, on the other hand, endow the kit with improved capacity in assessing the clinical status of a tested individual in a single test.